Cyclin B3 activates the Anaphase-Promoting Complex/Cyclosome in meiosis and mitosis - Garrido, Damien (PLoS Genet, 2020)
In mitosis and meiosis, chromosome segregation is triggered by the Anaphase-Promoting Complex/Cyclosome (APC/C), a multi-subunit ubiquitin ligase that targets proteins for degradation, leading to the separation of chromatids. APC/C activation requires phosphorylation of its APC3 and APC1 subunits, which allows the APC/C to bind its co-activator Cdc20. The identity of the kinase(s) responsible for APC/C activation in vivo is unclear. Cyclin B3 (CycB3) is an activator of the Cyclin-Dependent Kinase 1 (Cdk1) that is required for meiotic anaphase in flies, worms and vertebrates. It has been hypothesized that CycB3-Cdk1 may be responsible for APC/C activation in meiosis but this remains to be determined. Using Drosophila, we found that mutations in CycB3 genetically enhance mutations in tws, which encodes the B55 regulatory subunit of Protein Phosphatase 2A (PP2A) known to promote mitotic exit. Females heterozygous for CycB3 and tws loss-of-function alleles lay embryos that arrest in mitotic metaphase in a maternal effect, indicating that CycB3 promotes anaphase in mitosis in addition to meiosis. This metaphase arrest is not due to the Spindle Assembly Checkpoint (SAC) because mutation of mad2 that inactivates the SAC does not rescue the development of embryos from CycB3(-/+), tws(-/+) females. Moreover, we found that CycB3 promotes APC/C activity and anaphase in cells in culture. We show that CycB3 physically associates with the APC/C, is required for phosphorylation of APC3, and promotes APC/C association with its Cdc20 co-activators Fizzy and Cortex. Our results strongly suggest that CycB3-Cdk1 directly activates the APC/C to promote anaphase in both meiosis and mitosis.